EFFECTS OF COAL MINING ON FISHES OF MEGHALAYA, INDIA: A REVIEW - NATH, PRIYAM; DEKA, ADITY; TALUKDAR, MANOJ (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
Coal mining activities generate huge quantity of effluent containing tremendous amount of several metals, nitrate, sulphate, dissolved, and suspended solids as well as other harmful pollutants. These toxic effluents are regularly being released into the neighbouring ponds, lakes and rivers. Significant discharge of untreated coal mining effluent into the aquatic environment contributes to a variety of toxic effects on aquatic fauna including fish. Coal mining activities specifically in the region of Meghalaya located in North-east India is posing severe threats to the aquatic biota. The purpose of the paper is to pay special emphasis on the fish fauna that lives in this region that has large effluents of acid mine drainage. Many authors have previously described the different histopathological changes in a fish that suffer from severe toxicity of acid mine drainage. This study has been prepared taking into account the various works of different authors and is thus a review of their work. The whole aim of the study is to give a general idea that acid mine drainage from coal mines has tremendous impact on the fish fauna and may completely wipe out the population that thrives therein in the long run.